A prerequisite for patient centred care is empowering and engaging patients in the digital health: report from EFMI Special Topic Conference (STC) 2017 - de Lusignan, S (Academy of Medical Sciences of Bosnia and Herzegovina, 2017)
The European Federation for Medical Informatics (EFMI) held its Special Topic Conference (STC) in October 2017 in Israel. EFMI holds STC's to focus on a particular issue, whereas its major annual conference Medical Informatics Europe (MIE) has a much wider remit. This conference challenged the informatics community to engage patients in digital health. Examples of the gap in digital engagementfrom the conference contributions include: An app to connect parents to a paediatric emergency department was presented. We heard how comparisons between general practice and paediatrician led health systems were being compromised through the lack of available databases and that Europe needs a fit-for-purpose paediatric electronic health records (EHR). The public should be involved in shared EHR platform development. We were informedpatients preferred clinicians to use their mobile device and how the online community can be a source of research subjects. A visualisation tool is being developed to display data about attention deficit hyperactivity disorder (ADHD). On a more sombre note the conference remembered Assa Reichert, a long standing member of EFMI. Notwithstanding our reflections on Assa's service to EFMI and informatics, this conference provide a real opportunity to explore how digital health might empower patients.